2017
DOI: 10.1159/000480255
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes on Cone-Beam Computed Tomography during Balloon-Occluded Transcatheter Arterial Chemoembolization Using Miriplatin for Hepatocellular Carcinoma: A Preliminary Study

Abstract: Background/Aim: Balloon-occluded transcatheter arterial chemoembolization (B-TACE) using miriplatin (MPT) is anticipated as a new strategy for hepatocellular carcinoma (HCC). This study was aimed at evaluating the hemodynamic changes with/without balloon occlusion of the hepatic artery, correlation of cone-beam CT (CBCT) pixels, and CT value after B-TACE for HCC. Methods: A total of 52 patients with HCC, who underwent B-TACE using MPT in addition to the balloon-occluded CBCT hepatic arteriography, were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Three reports[ 30 - 32 ] have explored the hemodynamic changes assessed by balloon occlusion using CBCT and angiography-assisted CT. Ishikawa et al[ 30 ] reported that the CBCT pixel values of tumor enhancement increased after balloon occlusion in 37 of the 52 nodules, whereas it decreased in the remaining 15 nodules. Yoshimatsu et al[ 31 ] showed that the degree of tumor enhancement on selective CT during hepatic angiography (CTHA) increased after balloon occlusion in 3 of the 27 nodules, while it decreased in 11 nodules.…”
Section: Mechanism Of B-tacementioning
confidence: 99%
See 2 more Smart Citations
“…Three reports[ 30 - 32 ] have explored the hemodynamic changes assessed by balloon occlusion using CBCT and angiography-assisted CT. Ishikawa et al[ 30 ] reported that the CBCT pixel values of tumor enhancement increased after balloon occlusion in 37 of the 52 nodules, whereas it decreased in the remaining 15 nodules. Yoshimatsu et al[ 31 ] showed that the degree of tumor enhancement on selective CT during hepatic angiography (CTHA) increased after balloon occlusion in 3 of the 27 nodules, while it decreased in 11 nodules.…”
Section: Mechanism Of B-tacementioning
confidence: 99%
“…Asayama et al[ 32 ] also reported that 15 of the 35 nodules showed decreased enhancement or perfusion defects on CTHA with balloon occlusion. While the percentage of decreased tumor enhancement varied markedly among those studies, it remained a negative predictive factor for a dense LE accumulation[ 30 , 31 ] and short-term therapeutic effect[ 32 ]. It can be presumed that the blood flow from the occluded artery reduced and the blood flow from the collateral arteries relatively increased[ 31 , 32 ].…”
Section: Mechanism Of B-tacementioning
confidence: 99%
See 1 more Smart Citation
“…Kakuta et al [22] demonstrated that flow redistribution occurs immediately after balloon occlusion, since no significant differences were found in BOASP values measured immediately after and 5 min after balloon occlusion (p = 0.124). Hemodynamic changes were investigated also with contrast enhanced ultrasound (CEUS) in a case series of two patients [23] and with CT or CBCT post contrast acquisition with balloon deflated and inflated [24][25][26][27]. Inoue in 2019 [27] proposed the employment of a double balloon (a 5.2 Fr balloon inflated in proper hepatic artery and a selective 1.8 Fr in the tumor's feeder) in order to ensure a flow redistribution in those patients in which the target BOASP of >64 mmHg is not achieved by the sole microballoon occlusion.…”
mentioning
confidence: 99%
“…Ishikawa et al [16] described that balloon-occluded transcatheter arterial chemoembolization (B-TACE) using miriplatin is a new strategy for HCC. Therefore, they attempted to evaluate the hemodynamic changes with/ without balloon occlusion of the hepatic artery and correlation of cone-beam CT (CB-CT) pixels and CT value after B-TACE for HCC.…”
mentioning
confidence: 99%